Biomaterials for Bone Tissue Engineering 2020 - Bloise, Nora; Fassina, Lorenzo (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book presents recent advances in the field of bone tissue engineering, including molecular insights, innovative biomaterials with regenerative properties (e.g., osteoinduction and osteoconduction), and physical stimuli to enhance bone regeneration.